OSELTAMIVIR MEDICATION IN THE PEDIATRIC PRACTICE: THE REVIEW - A.B. Ivanyuk; S.A. Kolbin (Union of pediatricians of Russia, 2008)
Flu in children is characterized by high incidence, often development of complications, long virus extraction. Measures for its prophylaxis and treatment include the usage of vaccines and etiotropic medications, in particular, those of the neuraminidase inhibitor group which are considered to be efficient and safe in children. Oseltamivir is the most widespread drug of this group in the pediatric practice. The objective of this research was the analysis of foreign works devoted to the use of oseltamivir in children from the evidence based medicine viewpoint. as a result, two multicenter double blind placebo controlled trials were found, which included 1029 children other trials devoted to the study of different aspects of this problem. They showed that in children without co-morbidities, oseltamivir evidentially reducesthe duration of disease, duration of fever, cough, rhinitis and the frequency of complications; in case of bronchial asthma, however, these changes are below statistical significance. Oseltamivir shows high tolerability in children, and adverse events seldom occur.Key words: oseltamivir, neuraminidase inhibitors, children.